Sagrado feminino e mulheres de Àṣẹ na poesia de Elizandra Souza : uma experiência de tradução - Mattiello, Laura (2023)
This work centres on the Italian translation of Elizandra Souza's most recent poetry collection (2021). The translation issues relating to the elements of Afro-Brazilian culture, the realia and the Yoruba religious terms that permeate the black poet's verses triggered an interdisciplinary research process, based on field research in various candomblé terreiros. At the same time, the aim is to highlight the role of female leaders and the social structure of Brazilian candomblés in the construction of black feminism. The Sacred Feminine of the Yoruba cosmogony, together with the Iyalorixás, is explored as a possible guiding element in the literary work of the majority of Afro-descendant women writers. In the collection under translation, the numerous references to the Iyabás and the ancestors are conceived within a refined symbolic system, that originates from epistemologies of the African tradition, generally based on orality and non-written forms.